Synthesis and Characterization of New-Type Soluble ?-Substituted Zinc Phthalocyanine Derivative of Clofoctol - Dridi, Sabrine; Khiari, Jamel Eddine; Magna, Gabriele; Stefanelli, Manuela; Lvova, Larisa; Mandoj, Federica; Khezami, Khaoula (Mdpi, 2023)
In this work, we have described the synthesis and characterization of novel zinc (II) phthalocyanine bearing four 2-(2,4-dichloro-benzyl)-4-(1,1,3,3-tetramethyl-butyl)-phenoxy substituents on the peripheral positions. The compound was characterized by elemental analysis and different spectroscopic techniques, such as FT-IR, H-1 NMR, MALDI-TOF, and UV-Vis. The Zn (II) phthalocyanine shows excellent solubility in organic solvents such as dichloromethane (DCM), n-hexane, chloroform, tetrahydrofuran (THF), and toluene. Photochemical and electrochemical characterizations of the complex were performed by UV-Vis, fluorescence spectroscopy, and cyclic voltammetry. Its good solubility allows a direct deposition of this compound as film, which has been tested as a solid-state sensing material in gravimetric chemical sensors for gas detection, and the obtained results indicate its potential for qualitative discrimination and quantitative assessment of various volatile organic compounds, among them methanol, n-hexane, triethylamine (TEA), toluene and DCM, in a wide concentration range.
Keywords: phthalocyanines; solubility; gas sensors; quartz microbalances